A Systematic Comparison of In-Person and Video-Based Online Interviewing - Lobe, Bojana; Morgan, David L.; Hoffman, Kim (International journal of qualitative methods, 2022)
Due to the increasing popularity of online qualitative interviewing methods, we provide a systematically organized evaluation of their advantages and disadvantages in comparison to traditional in-person interviews. In particular, we describe how individual interviews, dyadic interviews, and focus groups operate in both face-to-face and videoconferencing modes. This produces five different areas for comparison: logistics and budget, ethics, recruitment, research design, and interviewing and moderating. We conclude each section with set of recommendations, and conclude with directions for future research in online interviewing.